(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Outside of traditional medicine, herbalists have a long history of usage. Improvements in analysis and quality control, as well as advancements in clinical research, are demonstrating usefulness of herbal medicine in the treatment and prevention of illness. Momordicacharantia (Bitter melon) is a climbing vine whose bitter leaves and green fruits have been used to treat cancer, diabetes, and a variety of infectious illnesses. It’s also a potent anti-HIV/AIDS weapon. Roots, according to Ayurveda, are beneficial in treatment of eye problems. Bitter, cooling, digestible, laxative, antipyretic, anthelmintic, appetizer, treats biliousness, blood disorders, anaemia, urinary discharges, asthma, ulcers, bronchitis, and other ailments Fruit is bitter, carminative, tonic, stomachic, aphrodisiac, anthelmintic, astringent to intestines, and helpful in the treatment of syphilis, rheumatism, spleen problems, and other ailments, according to Unani school of medicine. Bitter melon is well-known for its ability to help people with diabetes. Bitter melon contains a molecule that is chemically similar to insulin and is often referred to as p-insulin. Researchers have discovered that when taken consistently over a length of time, it has the potential to replace insulin in body. It also includes charantin, a steroidal saponin, peptides that are related to peptides, and some alkaloids that successfully regulate blood sugar levels.